Advancing Physical Therapy Practice through Curriculum Revision: The Malawi Experience - Beling, Janna; Chisati, Enock (Frontiers in Public Health, 2017)
Challenged health systems are a motivation for health education reform. Although resources-limited areas cover our planet, sub-Saharan Africa has the highest disease burden, yet the lowest health-care provider and medical school density of any region in the world. Malawi is among the most under-resourced countries in the world. While much of the data focus on dental, medical, and psychiatric service provision, physical therapists are also in short supply. Among the barriers to achieving the recommended standards for physical therapist education, African physiotherapists (the term for “physical therapists” in Africa) identify limited training opportunities, limited research education, and limited resources and funding. The purpose of this article is to describe an international partnership for strengthening the Malawian physiotherapist workforce capacity through curriculum revision in the Department of Physiotherapy at the University of Malawi’s College of Medicine.